Cardiac drug therapy - Khan, M. I. Gabriel (Saunders, 2000)
Univ. of Ottawa, Canada. Pocket-sized outline to drug therapeutics for every type of cardiovascular disease. Includes new and old drugs. This edition includes information on beta blockers, angiotensin 11 receptor blockers and ACE inhibitors, anti-platelet agents and stains and management of hypertension. For clinicians. Trim size: 8 x 5 inches. Previous edition: c1995. Softcover.
Keywords: kardiovaskulární látky; kardiologie; nemoci srdce; Heart Diseases; Cardiovascular Agents; kardiovaskulární nemoci; farmakoterapie; Cardiovascular Diseases; Drug Therapy; angiologie